‏Kalam e Majeed Amjad ka Tadveni Safar - Tasnim Kousar (بازیافت, 2024)
Majeed Amjad is a renowned name of modern Urdu poetry. He did not get the recognition he deserved in his lifetime. His formal introduction in the literary circles is due to Dr. Khawaja Muhammad Zakaria. Hecompiled Majeed Amjad's poetry as well as criticized Majeed Amjad's poetry in a constructive manner too. Apart from above said compilation, there are many other compilations of Majid Amjad's poetry butKhawaja Zakaria had close relations with Majid Amjad, due to which Khawaja Zakaria had access to the original sources to a great extent. In the article under review, the merits and demerits of the different compilations of Majeed Amjad's poetry and gradual process of compilation of his poetry is discussed. Through the comparative study of different compilations of Majid Amjad, it is tried to denote the authentic compilation of his poetry. Keywords: Majeed Amjad, Modern Urdu Poetry, Poetical structures, Modernity, Dr, Khwaja Zakria